Incidence and outcome of uveitic glaucoma in eyes with intermediate, posterior or panuveitis followed up to 10 years after randomization to fluocinolone acetonide implant or systemic therapy. - Kempen, John H. (Am J Ophthalmol, 2020)
PURPOSE: To evaluate long-term risk and outcomes of glaucoma in eyes with intermediate, posterior, and panuveitis managed with systemic or fluocinolone acetonide (0.59 mg, “implant”) therapy. DESIGN: Prospective Follow-up of the Multicenter Uveitis Steroid Treatment (MUST) Clinical Trial Cohort METHODS: Patients with intermediate, posterior or panuveitis randomized to implant or systemic therapy (corticosteroid plus immunosuppression in >90%) were followed prospectively for glaucoma incidence and outcome. RESULTS: Among 405 uveitic at-risk eyes of 232 patients (median follow-up=6.9 years), 40% (79/196) of eyes assigned and treated with implant and 8% (17/209) of eyes assigned and treated with systemic therapy (censoring eyes receiving an implant upon implantation) developed glaucoma (Hazard Ratio (HR)=5.9 (95% CI: 3.2, 10.8); p<0.001). Adjustment for IOP elevation during follow-up only partially mitigated the association of implant treatment with glaucoma incidence: HR=3.1 (95% CI: 1.6, 6.0); p=0.001. Among 112 eyes of 83 patients developing glaucoma, the five year cumulative incidence following diagnosis of sustained (2 or more consecutive visits) worsening of mean deviation by ≥6 dB was 20% (95% CI: 12%, 33%); five year cumulative incidence of sustained worsening of cup-to-disc ratio by ≥0.2 was 26% (95% CI: 17%, 39%). CONCLUSIONS: Implant has substantially higher risk of glaucoma than systemic therapy, a difference not entirely explained by post-treatment IOP elevation. Management of IOP elevation was effective in preventing worsening of glaucoma for the large majority of cases, but even under expert clinical management some glaucoma worsened. Uveitis cases should be monitored carefully for IOP elevation and glaucoma indefinitely.